From the University Reform Movement (MRU) enshrined in the Manifesto of Cordoba in 1918 and the nomination of the essential functions of the University: teaching, research and extension: a look CTS. - Viteri Briones, Telmo (Revista Universidad de Guayaquil, 2012)
Science, technology and society studies (STS) constitute an interdisciplinary field of work focused on the understanding of the social aspects of science and technology, both in terms of the economic, political or cultural factors that influence scientific and technological change, and in terms of the consequences of that same change for society and the environment". (Note by the editors, Science, Technology, Society and Culture... López Cerezo, José, Sánchez Ron, José).